Pemberdayaan Wanita Tunasusila Melalui Pendekatan Self Identity untuk Mengatasi Stigmatisasi - Pahar, Usman; Astriyanti (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2025)
This training program aims to empower marginalized women through a self-identity approach to overcome social stigma and enhance their economic independence. The program involved 20 participants from the Mattiro Deceng Women's Social Service Center (PPSKW) in Makassar. Data were collected through observation, in-depth interviews, and pre- and post-tests, then analyzed using a qualitative descriptive method to assess changes in self-awareness, social interaction, and economic independence among participants. The six-month training was carried out in six phases: preparation, partner mapping, personal and group approach, mentoring through self-identity, entrepreneurship development, and evaluation. The results show that empowering marginalized women through a self-identity approach has a significant positive impact on various aspects of the participants' lives. Overall, the self-identity approach combined with entrepreneurship training has proven to be an effective strategy for empowering marginalized women. This model can serve as a reference for other empowerment programs seeking to address social stigma and strengthen participants' economic independence.